The whole story: Rumors and science communication in the aftermath of 2012 Emilia seismic sequence - Crescimbene, Massimo; Todesco, Micol; La Longa, Federica; Ercolani, Emanuela; Camassi, Romano (Frontiers in Earth Science, 2023)
Controversies that stir the public debate on geological matters usually revolve around a few specific aspects, including the actual trigger of geological phenomena (i.e., natural vs anthropogenic), their predictability, and the trustworthiness of the experts who provide information and advice on the phenomena. A typical example of such difficulties is the case of the 2012 Emilia, Italy, seismic sequence which struck an area of relatively moderate seismic hazard. In that period, geophysical prospecting was planned to assess the potential of a reservoir for gas storage, near the town of Rivara. The low frequency of important seismic events in the area, associated with the ongoing industrial planning prompted widespread rumors of an anthropogenic origin of the 2012 earthquakes. Controversy also arose about the actual size of the seismic events: earthquakes magnitude can be computed with different methods, and its value depends on the type, number, and geographical distribution of the available seismic stations. As a result, different institutions commonly release different estimates of the earthquake magnitude, casting doubts on the reliability of each estimate. Since 2012, public concern has also been caused by the repeated occurrence of unusual phenomena in the area, such as ground heating or bubbling well waters. Popular belief tends to establish a causal link between particular phenomena and seismic activity, reinforcing the false conviction that seismicity could be predicted. In this work we present and discuss some of the activities that INGV pursued through the years to contrast rumors and disseminate correct scientific information. In the aftermath of the 2012 seismic sequence, INGV worked in collaboration with the National Department of Civil Protection, the local administrations, the University Network of seismic engineering, the Regional Healthcare System and local volunteer organizations. The organization of public meetings, the collection and analysis of widespread rumors and the creation of ad hoc outreach materials all contributed to reinforce the mutual trust between our research institute and the local population.